2020
DOI: 10.3390/ma13245604
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization and Characterization of Soda Residue-Fly Ash Geopolymer Paste for Goaf Backfill: Beta-Hemihydrate Gypsum Alternative to Sodium Silicate

Abstract: Solid waste soda residue (SR), as an industrial pollutant of water, air and soil environment, can be utilized to prepare the low-calcium fly ash (FFA)-based geopolymer paste activated by sodium silicate (NS) solution for goaf backfill. However, the high addition of NS produces the high cost and high strength of synthesized backfill material in the previous study. The objective of this research is to investigate the cost optimization method and performance evaluation of SR-FFA-based geopolymer backfill paste. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The SR was used with blend of FFA and alkali-activator solution to prepare the geopolymer grouting paste for goaf backfill [25]. The prepared paste occurs the chemical reaction of geopolymerization between Si-O and Al-O bonds to generate the mixtures of (Ca, Na)-containing aluminosilicate polymer gel (N,C)-A-S-H and calcium silicate hydrated gel C-S-H. Additionally, the SR also was used with FFA, beta-hemihydrate gypsum and alkali-activator solution, to manufacture the geopolymer slurry for goaf backfill [49]. The reaction mechanism of geopolymerization and hydration process still happen to form the coexistence of (N,C)-A-S-H and C-S-H gels, along with the hydration of gypsum.…”
Section: Discussionmentioning
confidence: 99%
“…The SR was used with blend of FFA and alkali-activator solution to prepare the geopolymer grouting paste for goaf backfill [25]. The prepared paste occurs the chemical reaction of geopolymerization between Si-O and Al-O bonds to generate the mixtures of (Ca, Na)-containing aluminosilicate polymer gel (N,C)-A-S-H and calcium silicate hydrated gel C-S-H. Additionally, the SR also was used with FFA, beta-hemihydrate gypsum and alkali-activator solution, to manufacture the geopolymer slurry for goaf backfill [49]. The reaction mechanism of geopolymerization and hydration process still happen to form the coexistence of (N,C)-A-S-H and C-S-H gels, along with the hydration of gypsum.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the poor cementation derived from the extremely low 28 day and 90 day UCS s, the fluidity of the mixture increases with the addition of FAI, but the pH and EC of the mixture decrease. In G1, high-calcium-based slags such as CS, SR, and BRS have a slow hydrated reaction with low-calcium FAII [ 5 , 7 , 37 ], and it is not obvious for GP, as an addition, to promote faster hydration to achieve better strength in a higher W/B of paste [ 30 ]. Subsequently, the nature of the hydration in G2 does not alter when low-calcium FAI is added to mixture G1.…”
Section: Resultsmentioning
confidence: 99%
“…The range study revealed that the fluidity and 28 d UCS increased and then decreased as the SR-FA ratio increased, with the greatest fluidity and strength occurring at an SR-FA ratio of 2:3 [ 7 ]. Then, 10% GP was substituted for Na 2 SiO 3 in SR-FA-based geopolymer paste for goaf backfill, with a high fluidity of 196–222 mm and a suitable 28-d UCS of 0.92 MPa [ 30 ]. It was determined that 10% GP improved fluidity and UCS sufficiently to meet the performance criteria of goaf backfill material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Quanta FEG450 scanning electron microscope was employed together with an energy dispersive spectroscopy (Hillsboro, OR, USA). The detection method was as follows: the area-scanning technique was used to determine the position of product gels in binders, and then the EDS spectra of representative points were obtained to analyze the gel products [17,19,42]. The samples were used for detection with gold spray pretreatment.…”
Section: Characterization Of Microstructure and Gel Productmentioning
confidence: 99%